Wetting State Transition of Laser Direct Writing Aluminum Surface Based on Coupling Effect of Micro/Nanoscale Characteristics - Wan, Qinlin (Langmuir : the ACS journal of surfaces and colloids, 2024)
Micro/nanostructured metal surfaces fabricated by laser direct writing (LDW) have been widely used in wettability-related fields. Previous studies focused on the effects of surface structural patterns or chemical composition on wettability, while the coupling mechanism and respective contributions of the two are not distinct. This paper reveals the coupling effect of micro/nanoscale characteristics on the wettability of LDW aluminum surfaces and elucidates the transition mechanism between wetting states on the surfaces with linear laser energy density. Through the contact angle experiments, a wetting state transition of the LDW surface is found from a more hydrophilic than pristine rose petal effect to lotus effect. Based on the bionic analysis method of the superhydrophobicity factors of lotus leaves, the contributions to the wettability of LDW surfaces are divided into the micro/nanoscale characteristics. The theoretical model for identifying the wetting state of a rough surface is proposed. Based on this model, the average Young's contact angle, θ̅Y, is calculated, which indicates the contribution of the nanoscale characteristics. During the transition process from rose petal effect to lotus effect, θ̅Y > 90° is a necessary condition for detachment from the rose petal effect, which is contributed by the high specific surface organic adsorption at the nanoscale. What is more, the wetting state determined by the microscale characteristics further enhances its hydrophobicity, leading to the lotus effect. Based on the wetting state identification model and the Cassie-Baxter equation, the change of micro/nanoscale characteristics on aluminum surfaces after LDW treatment is presented, and the influence of micro/nanoscale characteristics on the wetting state is decoupled and quantified. This research helps to coordinate the effects of surface structure and chemical composition on wettability in the design of specific wettability functional surfaces and can also be applied to other high heat density surface processing fields